PU.1 expression is modulated by the balance of functional sense and antisense RNAs regulated by a shared cis-regulatory element - Ebralidze, Alexander K; Guibal, Florence C; Steidl, Ulrich; Zhang, Pu; Lee, Sanghoon; Bartholdy, Boris; Jorda, Meritxell Alberich; Petkova, Victoria; Rosenbauer, Frank; Huang, Gang; Dayaram, Tajhal; Klupp, Johanna; et al. (Genes & development, 2008)
The transcription factor PU.1 is an important regulator of hematopoiesis; precise expression levels are critical for normal hematopoietic development and suppression of leukemia. We show here that noncoding antisense RNAs are important modulators of proper dosages of PU.1. Antisense and sense RNAs are regulated by shared evolutionarily conserved cis-regulatory elements, and we can show that antisense RNAs inhibit PU.1 expression by modulating mRNA translation. We propose that such antisense RNAs will likely be important in the regulation of many genes and may be the reason for the large number of overlapping complementary transcripts with so far unknown function.